Validity and reliability update of the Indonesian version of International Society for Prevention of Child Abuse and Neglect - Child Abuse Screening Tool (ICAST-C) - Meita Dhamayanti; Anne Dian Rachmawati; Anindita Noviandhari (Paediatrica Indonesiana, 2020)
Background In Indonesia, few screening tools for child abuse and neglect are available. The currently-favored tool was adapted from the International Society for Prevention of Child Abuse and Neglect (ISPCAN)-Child Abuse Screening Tool (ICAST-C) questionnaire, consisted of 5 domains child abuse and 59 items. Objective To re-evaluate the validity and reliability of the Indonesian version of ICAST-C. Methods A cross-sectional study was conducted 480 children aged 11–18 years from junior and senior high schools in Bandung, West Java, Indonesia. Subjects were selected using two-stage cluster sampling. A validity test using Spearman’s rank correlation with Rs >=0.3 was considered valid. A reliability test using Cronbach’s alpha formula with alpha score >=0.7 was considered reliable. Results Most items in the Indonesian version of ICAST-C were valid and reliable, except for the following 9 out of 59 items: “anyone in your home used alcohol”, “seen adults in your home use knives”, “insulted you by calling you dumb”, “in order stop or change behavior”, “forbade you from going out”, “pinched you”, “explained to you why something you did was wrong”, “gave you something else to do (in order to stop or change behavior)”, and “took away privileges or money”ICAST-C reliability was good (0.919), however domain of violence exposure (0.483) and neglect (0.445) were not so good Conclusion The updated Indonesian version of ICAST-C is considered valid, reliable as a screening tool for child abuse.